PERANCANGAN EMERGENCY RESPONSE PLAN PADA MULTI-APPROVAL CONCEPT OF SAFETY MANAGEMENT SYSTEM MANUAL TINGKAT INSTITUSI - Putriekapuja, Rany Adiliawijaya; Lestary, Dwi; Saputra, Surya Tri (Poltekkes Kemenkes Bandung, 2025)
Concern for occupational health and safety is important in the activity of an institution, including education, which has potential dangers and risks related to health and safety of all individuals in institutional environment. Indonesian Aviation Polytechnic Curug is an educational institution with various health and safety risks but currently does not have an integrated emergency response plan document at the institutional level. This research aims to prepare an emergency response plan document as a reference for handling emergencies, including emergency response procedures and all possible emergencies. The method used is Research and Development. This research began with the stages of identifying potential incidents, drafting an emergency response plan, carrying out validation, product trials through tabletop exercises, usage trials through full simulation, and mass production. The research results show that emergency response plan document can improve emergency teams' readiness and coordination. Evaluation of product trials resulted in average score above 80%, indicating high effectiveness in aspects of command, communication, and coordination between teams. The full simulation results that emergency response plan clarifies the roles and responsibilities of the emergency response team, even though there are challenges in the internal communication system that require the provision of communication facilities for each team. This institutional level emergency response plan product can be a comprehensive, easy to understand, and structured guide because it provides instructions on how to act in various emergency scenarios. Future research can analyze other aspects of occupational safety and health, such as psychological and social of emergency response teams.